The effect of early life events on glucose levels in first-episode psychosis - Garcia-Rizo, Clemente; Cabrera, Bibiana; Bioque, Miquel; Mezquida, Gisela; Lobo, Antonio; Gonzalez-Pinto, Ana; Diaz-Caneja, Covadonga M.; Corripio, Iluminada; Vieta, Eduard; Baeza, Inmaculada; Garcia-Portilla, Maria Paz; Gutierrez-Fraile, Miguel; et al. (Frontiers in Endocrinology, 2022)
First episode of psychosis (FEP) patients display a wide variety of metabolic disturbances at onset, which might underlie the latter increased morbidity and early mortality. Glycemic abnormalities have been previously related to pharmacological agents, however recent research highlights the impact of early life events. Birth weight (BW), an indirect marker of the fetal environment, has been related to glucose abnormalities in the general population over time. We aim to evaluate if BW correlates with glucose values in a sample of FEP patients treated with different antipsychotics. Two hundred and thirty-six patients were included and evaluated for clinical and metabolic variables at baseline, 2, 6, 12, and 24 months of follow-up. Pearson correlations and linear mixed model analysis were conducted to analyze the data. Antipsychotic treatment was grouped due to its metabolic risk profile. In our sample of FEP patients, BW was negatively correlated with glucose values at 24 months of follow-up [r=-0.167, p=0.037]. BW showed a trend towards significance in the association with glucose values over the 24-month period (F=3.22; p=0.073) despite other confounders such as age, time, sex, body mass index, antipsychotic type, and chlorpromazine dosage. This finding suggests that BW is involved in the evolution of glucose values over time in a cohort of patients with a FEP independently of the type of pharmacological agent. Our results highlight the importance of early life events in the later metabolic outcome of patients.